Performance Assessment to Measure Student’s Mathematical Proving Ability Based on the Abductive-Deductive Approach - Salsabila, Ellis; Rahayu, Wardani; Deniyanti Sampoerno, Pinta (KnE Social Sciences, 2020)
This study provides an overview of performance assessment instruments to measure students’ mathematical proving abilities based on the abductive-deductive approach. This is descriptive qualitative research of performance assessment instruments and their rubrics in measuring students’ mathematical proving abilities. The research method was literature study. The performance assessment instrument consists of essays designed to identify the mathematical proving abilities of students in mathematics courses. In this article, the examples are given for the Real Analysis class. The items of performance assessment were arranged referring to the abductive-deductive reasoning approach which has a pattern containing three main questions: 1) “What conditions can be obtained from the conclusion?” which was answered with abductive reasoning, 2) “What are the consequences that can be obtained from known facts?” which can be answered with deductive reasoning, and 3) “What conditions connect the conditions of conclusions and the implications of premise?” which can be answered with a key process of the mathematical statement proving process. Keywords: performance assessment, mathematical proving ability, abductivedeductive approach